Health Effects of Late-Career Unemployment. (January 2020) - Voss, Maren Wright; Wadsworth, Lori L.; Birmingham, Wendy; Merryman, M. Beth; Crabtree, Lisa; Subasic, Kathy; Hung, Man
Objective: Job loss has a demonstrated negative impact on physical and mental health. Involuntary retirement has also been linked to poorer physical and mental health outcomes. This study examined whether late-career unemployment is related to involuntary retirement and health declines postretirement.Method: Analysis was conducted using the 2000-2012 U.S. Health and Retirement Study (HRS) survey data with unemployment months regressed with demographic and baseline health measures on physical and mental health.Results: Individuals with late-career unemployment reported more involuntary retirement timing (47.0%) compared with those reporting no unemployment (27.9%). Late-career unemployment had no significant effect on self-reported physical health (β = .003, p = .84), but was significantly associated with lower levels of mental health (β = .039; p < .01).Conclusion: Self-reports of late-career unemployment are not associated with physical health in retirement, but unemployment is associated with involuntary retirement timing and mental health declines in retirement. Unemployment late in the working career should be addressed as a public mental health concern.